2022
DOI: 10.3389/fped.2022.883395
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of SARS-CoV-2 Viral Load and Clinical Evolution of Pediatric Patients in a General Hospital From Buenos Aires, Argentina

Abstract: BackgroundSARS-CoV-2 infection is associated with a wide range of clinical manifestations and severity. Pediatric cases represent <10% of total cases, with a mortality rate below 1%. Data of correlation between SARS-CoV-2 viral load in respiratory samples and severity of disease in pediatric patients is scarce. The cycle threshold (CT) value for the detection of SARS-CoV-2 could be used as an indirect indicator of viral load in analyzed respiratory samples.ObjectiveThe aim of this study was to describe … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 31 publications
0
8
0
Order By: Relevance
“…Reports of the ability of viral load to predict severe disease are contradictory [ 15 , 31 ]. In our cohort of children at risk for severe COVID-19, we found no difference in viral loads among those requiring hospitalization compared with those managed as outpatients.…”
Section: Discussionmentioning
confidence: 99%
“…Reports of the ability of viral load to predict severe disease are contradictory [ 15 , 31 ]. In our cohort of children at risk for severe COVID-19, we found no difference in viral loads among those requiring hospitalization compared with those managed as outpatients.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, the results of the present study highlight, interestingly, an association between low Ct values of qPCR detection of Salmonella on fecal samples and the severity of simultaneous clinical signs. Since the Ct value is known to be inversely proportional to the amount of target DNA in a sample and can therefore be used as a rough indirect estimate of its infectious load [ 44 ], the hypothesis of a higher fecal Salmonella shedding in more severely affected horses is plausible. The Ct value of qPCR has been shown to be related to the Salmonella load in various kinds of samples.…”
Section: Discussionmentioning
confidence: 99%
“…Quantitative real-time PCR (qPCR) provides quantitative results, and the cycle threshold value (Ct, number of cycles required for the PCR to detect the target microorganism) can be used as an indirect estimate of the load of the pathogen in the sample, as it has already been demonstrated in the detection of Salmonella enteritidis in feces of poultry [ 43 ]. In nasopharyngeal swabs of humans infected with SARS-CoV-2, the Ct values were correlated with viral loads and with the severity of the clinical signs, which further increased the clinical interest of this test [ 44 ]. Such a correlation has never been studied for salmonellosis, but could be useful to refine the rapid interpretation of the qPCR results.…”
Section: Introductionmentioning
confidence: 99%
“…A number of studies have revealed the association of SARS-CoV-2 viral loads with disease severity and outcomes in COVID-19 patients [ 20 , 21 ]. Notably, viral loads, especially in the plasma, are associated with laboratory abnormalities and mortality [ 22 ].…”
Section: Introductionmentioning
confidence: 99%